The opt-out family : how to give your kids what technology can't - Loechner, Erin (Zondervan Books, 2024)
"The Opt-Out Family unveils compelling research and startling insights from Erin Loechner's experiences as a social media trailblazer and former influencer, as well as practical and creative ways to transform your family's relationship with today's ever-evolving technology"--